2020
DOI: 10.3892/ol.2020.12145
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic effects of bisphenol A in breast and ovarian cancers (Review)

Abstract: Endocrine-disrupting chemicals (EDCs) are exogenous chemical compounds ubiquitously found in everyday life of the modern world. EDCs enter the human body where they act similarly to endogenous hormones, altering the functions of the endocrine system and causing adverse effects on human health. Bisphenol A (BPA), the principal representative of this class, is a carbon-based synthetic plastic, and a key element in manufacturing cans, reusable water bottles and medical equipment. BPA mimics the actions of estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 101 publications
0
39
0
Order By: Relevance
“…A link between BPA and the development of diabetes [ 39 ], anxiety, and depressive disorders [ 40 ], and an impaired functioning of the immune system has been found [ 41 ]. It can also contribute to infertility, endometriosis, and premature puberty [ 42 , 43 ]. However, BPA primarily exhibits hormone-like properties and, therefore, belongs to the class of endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%
“…A link between BPA and the development of diabetes [ 39 ], anxiety, and depressive disorders [ 40 ], and an impaired functioning of the immune system has been found [ 41 ]. It can also contribute to infertility, endometriosis, and premature puberty [ 42 , 43 ]. However, BPA primarily exhibits hormone-like properties and, therefore, belongs to the class of endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphenol A (BPA) affinity for, and binding to, estrogen receptors, poses another threat to fish health [ 79 ] as it has been repeatedly potentially associated with carcinogenesis processes [ 79 , 80 , 81 ]. Cervantes-Comacho et al [ 82 ] showed that exposure to sub-lethal doses of BPA (1, 10, 50, and 75 mg/L) caused significant DNA damage in the viviparous fish Blackfin goodea ( Goodea atripinnis ).…”
Section: Carcinogenic Potentialmentioning
confidence: 99%
“…cell migration and apoptosis, leading to neoplastic changes. Taking into account genetic mechanisms, BPA performs its functions through many oncogenic pathways, such as the STAT3, PI3K / AKT and MAPK pathways [23].…”
Section: Description Of Knowledgementioning
confidence: 99%